Becoming Joe Doakes: Averageness, Populism and Seriality in Robert Benchley's 'How to' Short Subjects. Issue 1 (1st October 2017) - King, Rob
Abstract : Over the course of the 1930s, the comic persona of Algonquin humorist Robert Benchley changed from that of a 'sophisticated' humorist to an 'average man'. This article situates Benchley's 'How to' short subjects for MGM (1935–44) within a broader public preoccupation with averageness that characterised the populist political rhetoric of New Deal-era America. In particular, it explores the function of seriality as a discursive trope conjoining the format of Benchley's MGM shorts to the broader construction of 'average' identities in the era's political culture.